Tackling the failure of microfinance efforts through amalgamating microfinance with charity: two viable alternatives in the context of Pakistan - Ashfaq Khan (Australasian Accounting, Business and Finance Journal, 2008)
The drastic shift in the microfinance paradigm during the early 1990s, when the donor community adopted a new approach as to the sustainability of microfinance institutions, changed the overall scenario of the paradigm. Instead of providing subsidized financial services to microfinance institutions (MFIs) for their life time, the donors started emphasizing self-sustainability on the part of MFIs through making them adopt principles of commercialism. The shift in the donors’ approach, although relieved of their burden to a considerable extent, gave rise to an increase in the interest rates on loans for the poor. Many scholars considered it as a drift from the primary mission. This conceptual paper presents two viable alternatives which, through amalgamating microfinance and charity principles, can potentially help the sector achieve the dual objective of boosting the supply of subsidized financial resources to the sector and ensuring the poor’s access to an affordable source of financial help.
Keywords: microfinance; self-sustainability; commercialism; donor community; subsidized; resources